Why do some wastewater treatment facilities work when the majority fail? Case study from the sanitation sector in Ghana - Murray, Ashley; Drechsel, Pay (Practical Action Publishing, 2011)
Failure is the norm for urban sanitation infrastructure in Ghana: of the rather substantial number of wastewater and faecal sludge treatment plants, with about 70 mostly decentralized systems throughout the country, less than 10 are operating effectively. This research presents an overview of the related sanitation situation in Ghana, and compares the few successful facilities with their failed counterparts in order to decipher the factors that enable the former to prevail. The research reveals important differences in the operation and maintenance (O&M) strategies, financing schemes and incentive structures in the successful versus unsuccessful facilities, which are probably not unique to Ghana. Based on the findings, we suggest a set of guiding questions for incorporation into the existing planning, funding or general decision-making framework in order to avoid commonly observed traps, which not only undermine progress in the delivery of sanitation services but also harshly affect environmental and public health.